FLOW AND FRACTURE MAPS FOR BASALTIC ROCK DEFORMATION AT HIGH TEMPERATURES - Rocchi V.; Sammonds P.R.; Kilburn C.R.J. (My University, 2003)
Understanding how the strength of basaltic rock varies with the extrinsic conditions of stress state, pressure and temperature, and the intrinsic rock physical properties is fundamental to understanding the dynamics of volcanic systems. In particular it is essential to understand how rock strength at high temperatures is limited by fracture. We have collated and analysed laboratory data for basaltic rocks from over 500 rock deformation experiments and plotted these on principal stress failure maps. We have fitted an empirical flow law (Norton's law) and a theoretical fracture criterion to these data. The principal stress failure map is a graphical representation of ductile and brittle experimental data together with flow and fracture envelopes under varying strain rate, temperature and pressure. We have used these maps to re-interpret the ductile-brittle transition in basaltic rocks at high temperatures and show, conceptually, how these failure maps can be applied to volcanic systems, using lava flows as an example.
Keywords: CREEP; FRACTURE; FLOW; PRINCIPAL STRESS MAPS; BASALT; DIABASE